Occupational choice: personality matters - Roger Ham; P. N. (Raja) Junankar; Robert Wells (Institute for the Study of Labor (IZA), 2009)
In modern societies, people are often classified as White Collar or Blue Collar workers: that classification not only informs social scientists about the kind of work that they do, but also about their social standing, their social interests, their family ties, and their approach to life in general. This analysis will examine the effect of an individual's psychometrically derived personality traits and status of their parents on the probability of attaining a white collar occupation over the baseline category of a blue collar occupation; controlling for human capital and other factors. The paper uses data from the Household Income and Labour Dynamics in Australia (HILDA) survey to estimate a random effects probit model to capture the effects on the probability of being in a white collar occupation. The results are then examined using the average marginal effects of the different conditioning variables over the whole sample. The analysis confirms the previous findings of human capital theory, but finds that personality and parental status also have significant effects on occupational outcomes. The results suggest that the magnitude of the average marginal effect of parental status is small and the effect of the personality trait conscientiousness is large and rivals that of education. Finally, estimates of separate models for males and females indicate that effects differ between the genders for key variables, with personality traits in females having a relatively larger effect on their occupational outcomes due to the diminished effects of education.
urn:nbn:de:101:1-2009051314
Keywords: J24; 330; Occupational choice; personality; human capital; dynasty hysteresis; Berufswahl; Persönlichkeitspsychologie; Familiensoziologie; Australien